Neuroanatomy - Douglas J. Gould (Philadelphia : Wolters Kluwer, 2020)
"BRS Neuroanatomy, sixth edition, is a concise review of human neuroanatomy intended for health professions students including medical and dental students preparing for their respective Boards and other examinations"
Keywords: Examination Questions; MEDICAL / Allied Health Services / Medical Assistants; Neuroscience MEDICAL / Test Preparation & Review Nervous System anatomy & histology